EFEKTIVITAS KONTRIBUSI SUMBER PENDAPATAN ASLI DAERAH DALAM MENDUKUNG KEMANDIRIAN FISKAL: STUDI KOMPARATIF PAJAK PENERANGAN JALAN DAN RETRIBUSI DAERAH - Syachbrani, Warka (Universitas Islam Negeri Alauddin Makassar, 2025)
This research aims to analyze the effectiveness of the collection and contribution of the two main sources of Regional Original Income (PAD), namely Street Lighting Tax (PPJ) and Regional Levies, in supporting the fiscal capacity of local governments. The research uses a quantitative descriptive approach with comparative study methods. The data used is the target and realization of Makassar City Street Lighting Tax revenue for the 2020–2024 period as well as the target and realization of Polewali Mandar Regency Regional Levy revenue for the 2022–2024 period. The analysis was carried out using the effectiveness ratio and contribution ratio to Original Regional Income. The research results show that Street Lighting Tax has a high level of effectiveness with an average of 93.88% and a contribution of 20.64% to PAD. In contrast, Regional Levies show a lower level of effectiveness with an average of 72.10% and a contribution of 16.39%. These findings indicate that tax-based PAD sources have a better ability to support regional fiscal capacity than levy-based PAD sources. This research contributes to the fiscal literature by showing the importance of optimizing regional revenue structures through strengthening revenue sources that have high effectiveness and contribution.